"That was a good shift": Interprofessional collaboration and junior doctors' learning and development on overtime shifts. Issue 4 (19th June 2017) - Johnson, Anya; Nguyen, Helena; Parker, Sharon K.; Groth, Markus; Coote, Steven; Perry, Lin; Way, Bruce
Abstract : Purpose: The purpose of this paper is to investigate a boundary spanning, interprofessional collaboration between advanced practice nurses (APNs) and junior doctors to support junior doctors' learning and improve patient management during the overtime shift. Design/methodology/approach: A mixed methods evaluation of an intervention in an adult tertiary referral hospital, to enhance interprofessional collaboration on overtime shifts. Phase 1 compared tasks and ward rounds on 86 intervention shifts with 106 "regular" shifts, and examined the effect on junior doctor patient management testing a model using regression techniques. Phase 2 explored the experience of the intervention for stakeholders. 91 junior doctors participated (89 percent response rate) on 192 overtime shifts. Junior doctors, APNs and senior medical professionals/administrators participated in interviews. Findings: The intervention was associated with an increase in self-initiated ward rounds by junior doctors, partially explained by junior doctors completing fewer tasks skilled nurses could also complete. The intervention significantly reduced doctors' engagement in tasks carried over from day shifts as well as first year (but not more experienced) junior doctors' total tasks. Interviews suggested the initiative reduced junior doctors' work pressure and promoted a safe team climate, situation awareness, skills, confidence, and well-being. Originality/value: Junior doctors overtime shifts (5 p.m. to 11 p.m.) are important, both for hospitals to maintain patient care after hours and for junior doctors to learn and develop independent clinical decision making skills. However, junior doctors frequently report finding overtime shifts challenging and stressful. Redesigning overtime shifts to facilitate interprofessional collaboration can improve patient management and junior doctors' learning and well-being.